Helping Students Revise Their Papers - Alinsangan, Paula (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Revision is a natural part of the writing process. Writers think over what they have produced and revise in an effort to express more clearly what they want to convey to their readers. Studies have shown that unskilled writers like most students have limited revision strategies and therefore need training to expand these strategies. However, when writing teachers have a limited view of revision in that they focus only on the correction of local level errors, they will be unable to give students the necessary training. This paper strongly recommends the need for teachers to help students improve their revision strategies. For teachers to be able to help, they will have to reshape their perceptions of writing and revision and to re-evaluate their teaching goals. Only then will they be able to provide their students the necessary classroom environment/or strategy training. Feedback being an important factor in improving student papers, the paper also presents different ways of appropriating feedback. The article ends by inviting teachers to engage in research that would lend insights on have different ways of feedback can best succeed in helping students improve their drafts.